(untitled) (London, 2017)
If you are a student conducting a systematic review for your dissertation or thesis, then this is the book for you! Written by an expert team of authors with years of experience in conducting systematic reviews and supervising students doing systematic reviews, the book provides a roadmap to guide you through the process.
Keywords: Research,Nghiên cứu; Methods,Phương pháp